Informality and urbanisation in African contexts: analysing economic and social impacts - Aline Afonso (dir.) (Centro de Estudos Internacionais, 2015)
This book gathers five papers presented to the ECAS$1 (B2013 proceedings. Following the theme of the Congress (3z(BAfrican dynamics in a multipolar world(3y(B, the challenge was to select among the 118 papers presented those which focused in the subjects of informality and space reconfiguration. The papers were selected from 4 panels: (3z(BWriting the world from another African metropolis: Luanda and the urban question(3y(B, (3z(BUrbanisation and poverty in mining Africa(3y(B, (3z(BUrban imaginaries in Africa(3y (Band (3z(BManagin...s
English
Keywords: urbanism; Africa; space